The Epidermal Growth Factor Receptor Increases Cytokine Production and Cutaneous Inflammation in Response to Ultraviolet Irradiation - El-Abaseri, Taghrid Bahig (Hindawi Publishing Corporation, 2013)
The epidermal growth factor receptor (EGFR) is activated in cutaneous keratinocytes upon ultraviolet (UV) exposure and has been implicated in ultraviolet-(UV-)induced inflammation and skin tumorigenesis. Egfr mutant mice and EGFR inhibitors were used to investigate the hypothesis that EGFR activation augments inflammation following UV irradiation. Topical treatment of mouse skin with the EGFR inhibitor AG1478 before UV exposure suppressed UV-induced erythema, edema, mast cell infiltration, and neutrophil infiltration. Genetic ablation of Egfr and EGFR inhibition by AG1478 also suppressed the increase in the proinflammatory cytokines tumor necrosis factor α (TNF-α), interleukin-1α, KC (murine IL-8), and cyclooxygenase-2 (COX-2) after UV exposure of cultured keratinocytes. Finally, genetic ablation of inhibition of EGFR in cultured keratinocytes decreased p38 activation after UV, while inhibition of p38 kinase reduced COX-2 expression after UV. These data demonstrate that EGFR regulates multiple aspects of UV-induced inflammation and suggest activation of p38 kinase leading to increased COX-2 and cytokine expression as one mechanism through which it acts.